Má oclusão em crianças e adolescentes com osteogênese imperfeita - Natalia Mendes de Matos Cardoso (2019)
Osteogenesis Imperfecta (OI) is a rare genetic disorder which affects connective tissue and it is caused by defects in type I collagen structure or synthesis. Alterations in collagen production might cause abnormal craniofacial growth and malformation of the teeth and dental arches. Among the malocclusions, individuals with OI have a high prevalence of crossbite, open bite and Class III malocclusion. This study aimed to compare the prevalence of malocclusion in children/adolescents with OI and without OI and to identify its associated factors. A cross-sectional study was performed of 39 individuals with OI and 39 without OI, aged from 3 to 17 years, and their parents/guardians. Children and adolescents with OI and without OI were matched by sex and age. They are treated in the Orthopedic and Pediatric outpatient clinics of a university hospital, in Belo Horizonte, southeastern Brazil. The instrument contained items on the individual, economic and oral-medical characteristics of the children. The clinical examination identified the type of breathing of the children / adolescents and the presence of dental anomalies, dental crowding, malocclusion (anterior open bite and anterior / posterior crossbite) and imperfect dentinogenesis (DI). In order to guarantee the reliability of the data, a theoretical training and the practical calibration of the examiners were carried out. Theoretical training was conducted through reading on the subject and images on slides. After this step, following a gold standard diagnosis, the practical calibration was performed. The kappa values obtained for each condition examined ranged from 0.82 to 0.96. The internal reliability was guaranteed by the test-retest of the instrument, which presented kappa values between 0.81 and 1.00. Then, the pilot study was carried out with 5 pairs of parents / guardians and children / adolescents with OI and 5 pairs without OI. After these phases the main study was started. This study was approved for the Research Ethics Committee of the Federal University of Minas Gerais. The mean age of children/adolescents was 7.9 years (± 4.5). When comparing the OI group and without OI, there was a statistically significant association between having OI and being diagnosed with dental anomalies (conoid teeth, fused/geminated teeth, clinical absence, rotation and microdontia) (p=0.001) and dental crowding (p=0.001). The presence of OI was statistically associated with anterior open bite (p=0.043), anterior crossbite (p=0.045) and posterior crossbite (p=0.004). In the OI group, the prevalence of anterior crossbite was associated with the use of bisphosphonates (p=0.036) and with the presence of ID (p=0.004). The presence of posterior crossbite was associated with the presence of ID (p=0.006). The anterior open bite was not statistically associated with the independent variables (p>0.05). It was concluded that the prevalence of dental anomalies and malocclusion was higher among children / adolescents with OI. In the group with OI, having DI was associated with the prevalence of anterior and posterior crossbite among children / adolescents. Using bisphosphonates was associated with anterior crossbite.